General insights into the diagnosis and clinical. Peruvian wart generates no splenomegaly - Arce, Julián (1921)
The diagnosis of tropical diseases, as all diseases in general is in the exact interpretation of the background and the information provided by clinical examination of the patient; ie, the diagnosis requires: 1° a very shrewd questioning while very accurate and detailed of all that relates to the life and health of the subject, considered in itself and in its relations with the environment ; 2° overall examination of the patient, organ by organ, function by function, to discover and record the symptoms and physical signs exist; and 3° harmonic and joint recovery of all data acquired serene certified and judiciously.